Application of High-Throughput Imaging Mass Cytometry Hyperion in Cancer Research - Le Rochais, Marion; Hemon, Patrice; Pers, Jacques-Olivier; Uguen, Arnaud (Frontiers in Immunology, 2022)
Imaging mass cytometry (IMC) enables tissue samples to be simultaneously analyzed for up to 50 parameters at subcellular resolution in order to detect proteins targeted by metal-conjugated antibodies and provide general architectural details in their native microenvironment. It may help to identify prognostic biomarkers, new therapeutic targets, biomarkers predictive of existing treatments’ efficacy, and to better understand the mechanisms of resistance to these treatments. Although its use has been growing in recent years, it faces some challenges. However, this does not affect its potential as a revolutionary tool in the life sciences for both discovery and healthcare applications, in particular in cancer research. This review proposes to provide an overview of the use of the IMC in cancer research studies.